Riesgos Psicosociales en una empresa de economía mixta de Santa Marta: Estudio Comparativo entre Área Operativa y Administrativa - Barros Rivera, Jhan Kevin; Trujillo Escobar, Julieth Andrea (Universidad Antonio Nariño, 2024)
This study focuses on psychosocial risk factors in the workplace, specifically in the operational and administrative areas of a company in Santa Marta. A questionnaire was applied to 100 employees to assess these risks and significant differences were found between the two areas. The current study is framed within the paradigm of positivism with a quantitative approach, with a comparative research level and a non-experimental type. The results highlight the need to implement measures to reduce work stress and improve the quality of life of employees. The research provides valuable information for decision-making and the promotion of a healthy work environment.